Introducing the Emotions-Affect Systems Elicitation (EASEL-3) index: A new tool for measuring affect regulation systems' activation - Pinto, A. M.; Figueiredo, C.; Geenen R.; Castilho, P.; Silva, J. A. P.; Morris, E. M. J.; Vanderhasselt, M.-A.; Kelly, A. C.; Naismith, I.; Ferreira, N.; Barnow, S.; Eickhoff, S. B.; et al. (Clinical Psychology and Psychotherapy, 2025)
Objective Although emotions pervade and influence individual and interpersonal functioning and well-being, their nature and taxonomy remain a bone of contention. The ‘three-circle’ model, comprising three dynamically interacting affect regulation systems (i.e., threat, drive, and soothing), provides a useful framework for aggregating emotions and understanding emotion (dys)regulation while closely supporting therapeutic intervention. Imbalances in the activation and (inter)action of these affect regulation systems have been implicated in a wide range of physical and mental disorders; however, there are currently no tools for quantifying each system's activation. The aim of this study was to develop a novel index of the three affect regulation systems: threat, drive and soothing. Method Three independent expert panels, composed of researchers in the ‘three-circle’ model, researchers in the field of affective science, and clinicians (N = 70), estimated the degree of activation of each affect regulation system induced by discrete emotions. Results Overall, agreement among experts was high regarding the emotions that mapped primarily onto each affect regulation system and the degree of the corresponding activation. These results constitute the basis for the Emotions-Affect Systems ELicitation Index (EASEL-3) index, which provides a continuous score of the estimated activation of the three systems. Conclusion and Discussion Although in need of field testing, the EASEL-3 index may prove valuable in research and clinical settings, opening new avenues on the measurement of the affect regulation systems, their correlates and associated outcomes, helping characterize and compare activation patterns across clinical populations and contexts, and informing the assessment and personalization of interventions.